First-principles study of ionic conductor Li3N - Kow, Yan Siong. (2012)
Since the 1960s, extensive researches have been done to search for promising materials for batteries in order to meet rising performance requirements of electronic devices. In order to achieve in high quality battery, it needs to have sufficiently high voltage, high durability (long-lasting), thin, easy for portable use and eco-friendly. Among various types of Lithium (Li) based material, Lithium Nitride (Li3N) is a type of fast ionic conductor, which is quite suitable as rechargeable battery material. Therefore, the purpose of this project is to investigate the Li vacancy formation energy of Li3N.